A Study to Evaluate Mothers’ Perceptions and the Effectiveness of an Awareness Program Aimed at Enhancing Knowledge About Behavioral Issues in Primary School Children Within a Specific Community in Haldwani, Uttarakhand - Gunajn Singh Bhakuni; Shashi Triphati; Rekha Koranga (International Journal of Community Health Nursing And Practices, 2024)
Background: Behavior is perceived in society as how an individual presents themselves in various situations. As a child grows, their development encompasses biological, psychological, and emotional changes that occur from birth. The parent-child relationship also evolves through daily, reciprocal interactions in different relational domains, such as attachment and authority, which lay the foundation for future interactions. These exchanges can significantly influence a child’s development across various areas, including emotional, physical, and intellectual growth. The importance of the parent-child relationship for optimal child outcomes and mental well-being throughout life has been well documented across different cultures and socio-economic backgrounds. Objectives: The study aimed to evaluate the effectiveness of an awareness program on mothers’ knowledge concerning behavioral issues in primary school children. Materials and methods: This mixed study was conducted on the mothers. The sample consisted of 50 mothers selected through the purposive sampling technique. Data gathering tools included a structured knowledge questionnaire. The awareness program was given to the mothers and after that post-test was carried out for them statistical tests such as paired t-test, and chi-square were used to interpret and analyze the data. Result: The mean post-test knowledge score was notably higher than the pre-test score, with a calculated ‘t’ value of 13.39, significantly exceeding the tabulated value of 49 (2.02) at p Conclusion: The study concluded that the awareness program was an extremely effective approach for enhancing mothers’ knowledge about behavioral problems in children.
Keywords: Behavioral problems; Knowledge; awareness program; effectiveness; mothers